Development of Digital Comic Interactive Media Toward Primary Students' Understanding of Concepts - Dhiva Hafiluddin Al Ghifary; Waspodo Tjipto Subroto; Mustaji Mustaji (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: The use of interactive media to understand the concept of material is a stimulation of the integration of all the senses in students, where the media will provide freedom to explore the material that is available in it freely, utilizing several unique features in Microsoft PowerPoint which the researchers then turned into an interactive learning tool for students, in its implementation students will be presented with learning media that integrates audio, video and visual components. Method: This research uses quantitative research with experimental methods. The population in this study was class VI students as experimental class research and VI B students as control class research, with a sample of class VI C students totaling 30 students for each sample on geographical characteristics and life in the ASEAN region. Results: This research produced media products in the form of interactive comics, which are proven to be able to increase students' conceptual understanding of material on geographical characteristics and life in the ASEAN region, as proven by the results of data processing using which proves that there is a significant influence. Novelty: There is a significant impact of the development of Digital Comic Interactive Media on Students' Conceptual Understanding of Elementary school is seen from the pretest and post-test results, which show that Ho is rejected and Hα is accepted. By rejecting Ho, it means that in this research, it is proven that the conceptual understanding of students who are given action is significantly different.